Dynamics of community structure and bio-thermodynamic health of soil organisms following subtropical forest succession. (15th February 2021) - Wang, Jun; Lu, Hongfang; Lin, Yongbiao; Campbell, Daniel E.; Cai, Hongyue; Ren, Hai
Abstract: Soil organisms play essential roles in maintaining multiple ecosystem processes, but our understanding of the dynamics of these communities during forest succession remains limited. In this study, the dynamics of soil organism communities were measured along a 3-step succession sequence of subtropical forests (i.e., a conifer forest, CF; a mixed conifer and broad-leaved forest, MF; and a monsoon evergreen broad-leaved forest, BF). The eco-exergy evaluation method was used as a complement to the classic community structure index system to reveal the holistic dynamics of the bio-thermodynamic health of soil organism communities in a forest succession series. Association between the self-organization of soil organisms, soil properties, and plant factors were explored through redundancy analyses (RDA). The results indicated that the biomass of soil microbes progressively increased in the dry season, from 0.75 g m −2 in CF to 1.75 g m −2 in BF. Microbial eco-exergy showed a similar pattern, while the community structure and the specific eco-exergy remained constant. Different trends for the seasons were observed for the soil fauna community, where the community biomass increased from 0.72 g m −2 to over 1.97 g m −2 in the dry season, but decreased from 3.94 g m −2 to 2.36 g m −2 in the wet season. Faunal eco-exergies followed a similar pattern. Consequently, the average annual biomass of the soil faunal community remained constant (2.17–2.39 g m −2 ) along the forest succession sequence, while the significant seasonal differences in both faunal biomass and eco-exergy observed at the early successional stage (CF) were insignificant in the middle and late forest successional stages (MF and BF). Both the dynamics of soil microbes and soil fauna were tightly correlated with tree biomass and with soil physicochemical properties, especially soil pH, moisture, total nitrogen, nitrate nitrogen, and organic matter content. Graphical abstract: Image 1 Highlights: Eco-exergy of soil microbe community gradually increased with forest succession. Soil fauna community remained constant with subtropical forest succession. Seasonal difference increased in soil microbes but decreased in soil fauna community. Soil organisms were tightly correlated with tree biomass and soil properties.